The ultimate filmmaker's guide to short films : making it big in shorts - Adelman, Kim, 1964- (Studio City, CA : M. Wiese Productions, 2004)
A comprehensive guide to creating short films that offers expert advice for every stage of the filmmaking process, including choosing the right project, deciding between film and video, producing a great film on a budget, avoiding common production mistakes, creating a press kit, marketing short films, and breaking into the industry.
Includes bibliographical references (p. 221-226) and index.
Adult
Keywords: Short films -- Production and direction; Motion pictures -- Production and direction; Short films